(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article meticulously explores the intricate relationship between the United States’ economy, sports culture, and mass media landscape. It aptly highlights the multifaceted connections that bind these three pillars, showcasing the profound impact each has on the others. The analysis begins with a keen examination of the economic ramifications of sports, elucidating how major events and sports franchises contribute not only to short-term economic boosts but also to long terminfrastructural development. The narrative seamlessly transitions to the realm of sports, delving into the cultural significance of athletics and the global influence wielded by American sports leagues and athletes. The article astutely recognizes the role of mass media as a catalyst in this triad, emphasizing how it not only reports on sports events but actively shapes the narrative, contributing to the creation of sports icons and fostering societal conversations. A noteworthy addition is the exploration of digital transformations in sports broadcasting and the emergence of sports betting as influential factors in reshaping the economic landscape. The article aptly considers the role of social media in athlete branding, underlining the paradigm shift in communication and its impact on individual and team dynamics